2003
DOI: 10.1074/jbc.m213182200
|View full text |Cite
|
Sign up to set email alerts
|

Different Properties of SEK1 and MKK7 in Dual Phosphorylation of Stress-induced Activated Protein Kinase SAPK/JNK in Embryonic Stem Cells

Abstract: Stress-activated protein kinase/c-Jun NH 2 -terminal kinase (SAPK/JNK), belonging to the mitogen-activated protein kinase family, plays an important role in stress signaling. SAPK/JNK activation requires the phosphorylation of both Thr and Tyr residues in its Thr-Pro-Tyr motif, and SEK1 and MKK7 have been identified as the dual specificity kinases. In this study, we generated The SAPK/JNK 1 is a member of the family of mitogen-activated protein kinase (MAPK). This MAPK is activated not only by many types of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 22 publications
(35 reference statements)
2
56
1
Order By: Relevance
“…Comparison of MKK4 and MKK7 in the developing brain MKK7 and MKK4 are both JNK activators, and complete activation of JNK requires the activities of both of these kinases (Kishimoto et al, 2003). In our Mkk7 flox/flox Nestin-Cre mice, phosphorylated JNK was markedly reduced despite an upregulation of MKK4 (Fig.…”
Section: Role Of Mkk7 In Neuronal Differentiationmentioning
confidence: 69%
“…Comparison of MKK4 and MKK7 in the developing brain MKK7 and MKK4 are both JNK activators, and complete activation of JNK requires the activities of both of these kinases (Kishimoto et al, 2003). In our Mkk7 flox/flox Nestin-Cre mice, phosphorylated JNK was markedly reduced despite an upregulation of MKK4 (Fig.…”
Section: Role Of Mkk7 In Neuronal Differentiationmentioning
confidence: 69%
“…This is supported by studies demonstrating that TNFa and IL-1 preferentially activate MKK7 in vitro and in cells (Finch et al, 1997;Lawler et al, 1997;Moriguchi et al, 1997;Tournier et al, 2001). In contrast, it was observed in Mkk4À/À and Mkk7À/À ES cells and MEFs that both MKK4 and MKK7 make similar contributions to JNK activation in response to a number of environmental stresses including UV radiation, heat shock and osmotic shock (Tournier et al, 2001;Kishimoto et al, 2003). Although the studies described above provided strong genetic evidence to support the role of MKK4 as a JNK activator in vivo, it had been less clear whether MKK4 could regulate p38 activity in vivo.…”
Section: Biochemical Properties Of Mkk4mentioning
confidence: 80%
“…These observations led to the hypothesis that JNK isoforms are activated synergistically by MKK4 and MKK7 (Lawler et al, 1998;Fleming et al, 2000;Lisnock et al, 2000). Some in vivo evidence to support this model has come from studies using mouse embryonic stem (ES) cells and mouse embryonic fibroblasts (MEFs) that feature targeted deletions of the Mkk4 and Mkk7 genes (Tournier et al, 2001;Wada et al, 2001;Kishimoto et al, 2003). These studies also demonstrated that distinct stimuli might differentially utilize MKK4 and MKK7.…”
Section: Biochemical Properties Of Mkk4mentioning
confidence: 99%
“…JNK is activated by many types of external stresses, including changes in osmolarity, heat shock, and UV irradiation, and this activity is regulated via the phosphorylation of particular tyrosine and threonine residues located in the kinase domain. JNK phosphorylation is catalyzed by two dual-specificity kinases, MKK4 3 and MKK7, that act in a synergistic manner (3,4). Although most often activated in response to stress, phosphorylated JNK has been detected in unstressed cultured cells and in isolated mouse tissues, such as the brain (5,6), indicating the importance of JNK signaling in physiological processes other than cellular stress responses.…”
mentioning
confidence: 99%